Efficacy of cloxacillin versus cefazolin for methicillin-susceptible Staphylococcus aureus bacteraemia (CloCeBa): study protocol for a randomised, controlled, non-inferiority trial. Issue 8 (1st September 2018) - Burdet, Charles; Loubet, Paul; Le Moing, Vincent; Vindrios, William; Esposito-Farèse, Marina; Linard, Morgane; Ferry, Tristan; Massias, Laurent; Tattevin, Pierre; Wolff, Michel; Vandenesch, François; Grall, Nathalie; et al.
Abstract : Introduction: Methicillin-susceptible Staphylococcus aureus (MSSA) bacteraemia is a common and severe disease responsible for approximately 65 000 deaths every year in Europe. Intravenous antistaphylococcal penicillins (ASP) such as cloxacillin are the current recommended antibiotics. However, increasing reports of toxicity and recurrent stock-outs of ASP prompted healthcare providers to seek for alternative antibiotic treatment. Based on retrospective studies, cefazolin, a first-generation cephalosporin, is recommended in patients at risk of severe ASP-associated toxicity. We hypothesised that cefazolin has a non-inferior efficacy in comparison to cloxacillin, with a better safety profile for the treatment of MSSA bacteraemia. Methods and analysis: The CloCeBa trial is an open-label, randomised, controlled, non-inferiority trial conducted in academic centres throughout France. Eligible patients are adults with MSSA bacteraemia without intravascular device or suspicion of central nervous system infection. Patients will be randomised (1:1) to receive either cloxacillin or cefazolin by the intravenous route, for the first 14 days of therapy. The evaluation criteria is a composite criteria of negative blood cultures at day 5, survival, absence of relapse and clinical success at day 90 after randomisation. Secondary evaluation criteria include both efficacy and safety assessments. Three ancillary studies are planned to describe the epidemiology of β-lactamase encoding genes, the ecological impact and pharmacokinetic/pharmacodynamic parameters of cefazolin and cloxacillin. Including 300 patients will provide 80% power to demonstrate the non-inferiority of cefazolin over cloxacillin, assuming 85% success rate with cloxacillin and taking into account loss-to-follow-up, with a 0.12 non-inferiority margin and a one-sided type I error of 0.025. Ethics and dissemination: This protocol received authorisation from the ethics committee Sud-Est I on 13 November 2017 (2017-87-PP)and French National Agency for Medicines and Health Products (170661A-43). Results will be disseminated to the scientific community through congresses and publication in peer-reviewed journals. Trial registration number: NCT03248063 and 2017-003967-36.